2000
DOI: 10.1023/a:1008369812295
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of unknown primary site: Phase II trials with docetaxel plus cisplatin or carboplatin

Abstract: Docetaxel and cisplatin (study A) is an active combination in carcinoma of unknown primary site, but associated with substantial gastrointestinal toxicity. A combination of docetaxel plus carboplatin (study B) is better tolerated and produced a similar response rate, median survival and one-year survival. Comparative phase III trials will be necessary to unequivically prove a survival advantage for any form of therapy in these patients. However, the survival for patients with carcinoma of unknown primary site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 8 publications
3
71
1
Order By: Relevance
“…The primary efficacy endpoint for this trial was survival; secondary endpoints included the objective response rate and progression-free survival duration. Standard firstline therapy with paclitaxel and carboplatin produces response rates of approximately 30%, and median survival time of approximately 9 months in patients with CUP [1][2][3][4]. In evaluating this new regimen, a higher proportion of patients alive at 9 months, 70% with the investigational combination versus 50% (expected with paclitaxel and carboplatin alone), was considered to be a result supporting further development of this regimen.…”
Section: Statistical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary efficacy endpoint for this trial was survival; secondary endpoints included the objective response rate and progression-free survival duration. Standard firstline therapy with paclitaxel and carboplatin produces response rates of approximately 30%, and median survival time of approximately 9 months in patients with CUP [1][2][3][4]. In evaluating this new regimen, a higher proportion of patients alive at 9 months, 70% with the investigational combination versus 50% (expected with paclitaxel and carboplatin alone), was considered to be a result supporting further development of this regimen.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…Empiric chemotherapy with taxane-platinum regimens is widely used for these patients. However, these regimens are only moderately effective, producing response rates of 30%-40%, with 1-and 2-year survival rates of approximately 40% and 20%, respectively [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…By restricting diagnostic procedures to a minimum, and with an early start of chemotherapy, median survival has improved from 3 -6 months of the past (Altman and Cadman, 1986;Alberts et al, 1989) to around 1 year in recently reported series (Briasoulis et al, 2000;Greco et al, 2000a).…”
mentioning
confidence: 99%
“…25 Hopefully, these reports will be the first step toward new progress in the management of patients with CUPs. 12 ViAM 57 30 7 De Campos et al 13 VACy 40 8 4 Hainsworth et al 14 PECa 53 47 13 Lofts et al 15 FcC 44 27 4 Parnis et al 16 FcEpC 43 19 6 Greco et al 17 DC …”
Section: Discussionmentioning
confidence: 99%